The Impact of Perceived Value of Jamu Towards the Millennial Purchase Decision: The Case Study of Generation Z - Putra, Yosafat; Abryanto, Rano (Journal Akademik Universitas Swiss German, 2021)
The aim of this research is to identify the impact of perceived value of Jamu towards the millennial purchase decision in the case study of generation Z. The indicators use for perceived value are awareness, perception, and family environment. As for purchase decision, the indicator used are consumer behavior and purchase motivation. The data were collected from 125 who have previously consumed Jamu. Simple linear regressions and descriptive data analysis were used to examine the data collected. The findings indicate that perceived value of Jamu significantly impacts the millennial generation and with descriptive data analysis each indicator were examined. Among all indictors of perceived value, perceptions have the highest impact towards the millennial purchase decision.